Globalizing the boardroom among family-controlled companies listed on bursa Malaysia- the effects of corporate governance on firm performance - Ng, Veronica Zi Ching (2019)
This research aims to determine if corporate governance affects firm performance among family-controlled listed companies on Bursa Malaysia with globalized boardroom after the implementation of Malaysia Code on Corporate Governance (MCCG) 2012 and The Code 2012. In this research, all family-controlled companies listed on Bursa Malaysia from the year 2013 to 2018 are obtained from book “Family Controlled Companies in Bursa Malaysia”. The sample size includes 240 firm year observations. Panel data analysis which includes fixed and random effect model as well as Hausman test, are used in this research to analyse the effect between CG mechanisms (Board size, Number of independent directors, CEO duality, Number of women directors, Number of foreign directors, Number of directors with foreign qualifications and Audit committee size) and firm performance, as measured by return on assets (ROA), return on equity (ROE) and Tobin’s Q. A liberty is also taken to run multiple linear regressions (MLR). According to the panel data analysis, it is found that there is no significant effect between corporate governance and firm performance of family-controlled companies listed on Bursa Malaysia with globalized boardroom. The same results were also being found in using multiple linear regressions. Thus, this research is helpful in providing further insights of corporate governance practices to the government, policy makers, stakeholders, investors and banks.